2012
DOI: 10.1111/j.1530-9290.2012.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use in Growing China

Abstract: Summary Natural resources provide the basis for our life on Earth. This article presents the accounts of China's direct material input (DMI) during 1998–2008. Using decomposition, we examine factors that have influenced changes in recent resource use in China. China's resource demand in 2011–2015 is projected, based on China's 12th Five‐Year Plan. Finally, effective policies to restrain China's resource demand are discussed with the following conclusions: (1) During 1998–2008, China's DMI doubled, from 11 giga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…In 1995, China accounted for only 4.7 per cent of worldwide crude steel production (IISI, 1996). We can confirm the results of Wang et al (2012), who found that raising material efficiency in China reduced material use.…”
Section: Country-specific Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In 1995, China accounted for only 4.7 per cent of worldwide crude steel production (IISI, 1996). We can confirm the results of Wang et al (2012), who found that raising material efficiency in China reduced material use.…”
Section: Country-specific Resultssupporting
confidence: 90%
“…Without structural change and the efficiency gains dampening it, Chinese material use would have five-folded from 1995 to 2008. Wang et al (2012), who investigate China's DMI from 1998 to 2008, find that the use of metallic minerals grows particularly strongly. This coincides with China taking a dominant role in many upstream industries.…”
Section: Country-specific Resultsmentioning
confidence: 99%
“…资源科学, 2017, 39 (10) : 1942-1955. [Dai T J, Wang W J, Liu R. Spatio-temporal variation of resource and environmental pressure in China [J]. Resources Science, 2017, 39 (10) : 1942-1955 、 李刚等 [5, 6] 、 刘敬智等 [7] 、 徐明等 [8] 、 王鹤鸣 等 [9] 均研究了中国不同时期的物质流动情况。随着 国家层面物质流分析方法逐渐成熟, SERI (Sustain- [10] 。 此后, 北京 [11] 、 陕西 [12] 、 辽宁 [13] 、 安徽 [14] 、 天津 [15] 、 上海 [16] 、 广东 [17, 18] 、 江苏 [19, 20] 、 海南 [21] 、 常州市武进区 [22] 、 张掖 [23] 、 邯郸 [24] 、 青岛 [25] 、 吉林四平 [26] 、 厦门 [27] 、 京津冀 [28] 》 [33] 《中国林业年鉴 (1993-2015) 》 [34] 《中国农业年鉴 (1993-2015) 》 [33] 《中国农业年鉴 (1993-2015) 》 [33] 《中国农业年鉴 (1993-2015) 》 [33] 《中国能源统计年鉴 (1991-2015) 》 [36] 《中国矿业年鉴》 [37] 和各省份矿产资料 《中国矿业年鉴》 [37] 和各省份矿产资料 《中国统计年鉴 (1993-2015) 》 [38] 《中国环境年鉴 (1993-2015) 》 [40] 《中国环境年鉴 (1993-2015) 》 [40] 《中国能源统计年鉴 (1991-2015) 》 [36] 《中国环境年鉴 (1993-2015) 》 [40] 《中国统计年鉴 (1993-2015) 》 [38] 《中国统计年鉴 (1993-2015) 》 [38] 《中国农业年鉴 (1993-2015) 》 [33] 《中国农业年鉴 ( 估算, 估算方法见参考文献 [43][44][45] 无 估算, 估算方法见参考文献 …”
unclassified
“…However, while these resouces provide us convenience, the using of them also brings pressure on the environment. Since Chinese economic reform, both GDP and resource consumption have increased dramatically over the past decades [1,2,3,4]. Therefore, the case of China provides a timely example of the relationship between economic growth and resource consumption during its economic transition process.…”
Section: Introductionmentioning
confidence: 99%